PENGARUH SISTEM INFORMASI AKUNTANSI PEMBELIAN BAHAN BAKU DAN PENGENDALIAN INTERN PEMBELIAN BAHAN BAKU TERHADAP EFEKTIVITAS PERSEDIAAN BAHAN BAKU PADA PT.IPHA LABORATORIES - Adawiah, Hoeriah Rabiatul (Jurusan Akuntansi Fakultas Ekonomi Universitas Langlangbuana Bandung, 2018)
Accounting system of raw material purchase and internal control of raw material purchases become an important part in a manufacturing industry in order to achieve effectiveness of raw material inventory used. This study aims to examine the influence of accounting information system purchases of raw materials and internal control purchases of raw materials partially to the effectiveness of raw materials inventory. This research employs survey method towards 30 employee’s participants. The primary data was obtained by means of questionnaire at likert-scale, in which its validity and reliability had been tested in advance. Methods of analysis used in this research is descriptive method and verification method. Result of research indicate that accounting system of raw material accounting purchase equal to 34,6% and internal control influenced 46,8% toward effectiveness of raw material inventory and the rest come from other factor which is not examined by researcher.